Dukungan Sosial dan Beban Pengasuhan pada Orang Tua Anak Berkebutuhan Khusus - Fitria Dian Rahmayanti; Farra Anisa Rahmania; Syarifah Na'imi Anisa; Fuad Nashori (INSAN Jurnal Psikologi dan Kesehatan Mental, 2022)
This study aimed to examine the association between social support and burden of care among parents of children with special needs. Data were collected using the Multidimensional Scale of Perceived Social Support (MSPSS) to measure perceived social support and the Burden Scale for Family Caregivers (BSFC) to measure perceived burden of care. The analysis utilized the Pearson’s correlation technique. Results indicated significant association between social support and burden of care. This finding highlights the importance of support from family, friends, and significant others in the management of perceived burden of care among parents of children with special needs.